Studies on the genus Chrysodema (Coleoptera: Buprestidae: Chrysochroinae) part I. - Frank, David; Sekerka, Lukáš (Zootaxa, 2020)
Subgeneric classification of Chrysodema Laporte de Castelnau & Gory, 1835 is revised and following synonymy is established: Chrysodema=Cyalithoides Fisher, 1922 syn. nov.; Pseudochrysodema Saunders, 1874=Leganya Hołyński, 1994 syn. nov.,=Marcsikiella Hołyński, 2014 syn. nov. Four subgenera are recognized as valid: Chrysodema s. str., Gelaeus Waterhouse, 1905, Pseudochrysodema Saunders, 1874, and Thymedes Waterhouse, 1905, and a key to the subgenera is given. Four species-groups are established in the subgenus Chrysodema s. str.: C. aeneoviolacea-group, C. aurostriata-group, C. eximia-group, and C. sonnerati-group. All known species, except the currently accepted synonyms of Chrysodema (Chrysodema) eximia Laporte de Castelnau & Gory, 1835, included in these groups are revised based on comparative study of extensive material including types of all described taxa. Three new species and one subspecies are described: Chrysodema (Chrysodema) dany sp. nov. from Haruku Island, Indonesia; C. (C.) gottwaldi sp. nov. from Palawan Island, Philippines; C. (C.) lewisii nakatai subsp. nov. from Yaeyama Islands, Japan; and C. (C.) vrabeci sp. nov. from Thailand and Laos. Chrysodema (C.) aeneoviolacea Deyrolle, 1864 stat. rev., C. (C.) dohrnii Saunders, 1874 stat. rev., and C. (C.) fuscitarsis Kerremans, 1895 stat. rev. are removed from synonymy with C. (C.) mniszechii Deyrolle, 1864; C. (C.) tonkinea Kerremans, 1909 stat. rev. is removed from synonymy with C. (C.) aurostriata Saunders, 1866. Three new synonymies are established: C. (C.) aeneoviolacea=C. (C.) elongata Kerremans, 1900 syn. nov.=C. (C.) keyensis Théry, 1923 syn. nov. (the latter was formerly synonym of C. (C.) elongata); C. (C.) dohrnii=C. (C.) fairmairei Kerremans, 1895 syn. nov. (formerly synonym of C. (C.) mniszechii). Neotype is designated for C. (C.) sonnerati Laporte de Castelnau & Gory, 1835 and lectotypes are designated for following taxa to ensure their correct application and recognition in future: C. (C.) aurostriata, C. (C.) fairmairei, C. (C.) fuscitarsis, C. (C.) sumatrensis Kerremans, 1895, C. (C.) tonkinea, C. (C.) yerburyi Waterhouse, 1905, C. (P.) coelestina Obenberger, 1922, and C. (P.) inslabilis Deyrolle, 1864. Additionally, dark species of the subgenus Pseudochrysodema are revised and as a result C. (P.) coelestina stat. rev. and C. (P.) instabilis stat. rev. are removed from synonymy with C. (P.) radians (Guérin-Méneville, 1830) and a new species C. (Pseudochrysodema) jakli sp. nov. is described from Timor Island, Indonesia. All herein included taxa are illustrated with colour photographs of habitus and the male aedeagus when available. All new taxa are diagnosed and a key to species of the C. aeneoviolacea-group is given.